Integration of Charles Peirce's philosophy into information science - Puerta-Díaz, Mirelys [UNESP]; Manhique, Ilídio Lobato Ernesto [UNESP]; Casarin, Helen de Castro Silva [UNESP]; Martínez-ávila, Daniel (My University, 2021)
The purpose of the study was to understand the integration of Charles Peirce's philosophy into information science. From a methodological point of view, it is a qualitative and quantitative study based on bibliometric techniques. The bibliographic data were obtained from four databases, two specifically related to information sciences: ProQuest – LISA Information Sciences Libraries and Abstracts, and the reference database for articles from information sciences journals; and two multidisciplinary databases: Scopus and Web of Science. Results show that Peircean philosophy is gradually consolidating as an important theoretical contribution in information sciences studies and publications, considering the relatively significant number (114) of publications retrieved from the aforementioned databases. These studies address pragmatism in research about knowledge management, information systems, information philosophy and knowledge organization, particularly as related to understanding or the inferential indexing process in information systems. The article concludes that there is a growing interest by the information sciences scientific community to develop Peirce's philosophy in a holistic manner, not limited to the first level of Peircean semiotics and speculative grammar, for it also includes studies dealing with inference, a process related to pure logic.
Integración de la filosofía de Charles Peirce en la Ciencia de la Información
Keywords: Charles Sanders Peirce; Information sciences; Metric studies of information; Peircean semiotics; Pure logic